Analysis of the Implementation of Discounted Cash Flow and Multiple Methods in Determining the Fair Value of Company Shares Related to the Initial Public Offering (IPO) Plan Case Study: PT XYZ - Fadli Rahman; Dony Abdul Chalid (Green Publisher Indonesia, 2025)
This study explores the implementation of stock valuation approaches, specifically the Discounted Cash Flow (DCF) and Multiples Valuation methods (P/E, EV/EBITDA), to determine the intrinsic value of PT XYZ shares in the context of its planned Initial Public Offering (IPO). Although stock valuation is a crucial element in the IPO process, most previous literature focuses on public companies and specific industry sectors, with limited discussion on state-owned construction enterprises (BUMN Karya) within the construction sector. This study contributes theoretically to the stock valuation literature in the construction services sector through a qualitative approach using an exploratory case study on PT XYZ. The DCF analysis is conducted by projecting cash flows using the Free Cash Flow to the Firm (FCFF) approach, discounted by the Weighted Average Cost of Capital (WACC), and estimating the share value based on market multiples (P/E and EV/EBITDA). The study also conducts scenario analyses (pessimistic, moderate, optimistic) and sensitivity analyses on key variables such as revenue and cost of goods sold (COGS) to assess the robustness of the valuation under varying assumptions. The results show that the intrinsic value of the shares based on the DCF method ranges from Rp6,627 to Rp28,239 per share, while the multiples valuation yields a range between Rp15,786 and Rp16,868, closely aligning with the moderate DCF scenario result of Rp15,880. These findings highlight the importance of valuation approaches in generating more ideal and realistic share price estimates prior to an IPO.